Pengaruh Pemanfaatan Teknologi Informasi dan Komitmen Organisasi terhadap Kualitas Laporan Keuangan Daerah pada Pemerintah Daerah Kota Sungai Penuh - Ayola, Pebiana; Fitra, Halkadri (Universitas Negeri Padang, 2025)
This study aims to determine the effect of information technology utilization and organizational commitment on the quality of regional financial reports in the local government of Sungai Penuh City. The population in this study were 40 SKPDs in Sungai Penuh City. The method of determining the sample using purposive sampling method with a saturated sample of 82. The data analysis method used is multiple linear regression analysis. The results showed that: 1) Utilization of information technology has a significant effect on the quality of regional financial reports in the local government of Sungai Penuh City. 2) Organizational commitment has no significant effect on the quality of regional financial reports in the local government of Sungai Penuh City. For future research, researchers suggest adding data collection techniques with direct interviews, adding other variables to prove the consistency of research result, and expanding the research object so that it can be generalized.